ANAC017 Coordinates Organellar Functions and Stress Responses by Reprogramming Retrograde Signaling. Issue 1 (14th March 2019) - Meng, Xiangxiang; Li, Lu; De Clercq, Inge; Narsai, Reena; Xu, Yue; Hartmann, Andreas; Claros, Diego Lozano; Custovic, Eddie; Lewsey, Mathew G.; Whelan, James; Berkowitz, Oliver
Abstract : Overexpression of ANAC017 in Arabidopsis leads to restricted growth, cell death, and early senescence due to impaired organellar retrograde signaling and transcriptomic reprogramming. Abstract: Mitochondria adjust their activities in response to external and internal stimuli to optimize growth via the mitochondrial retrograde response signaling pathway. The Arabidopsis ( Arabidopsis thaliana ) NAC domain transcription factor ANAC017 has previously been identified as a regulator of the mitochondrial retrograde response. We show here that overexpression of ANAC017 in Arabidopsis leads to growth retardation, altered leaf development with decreased cell size and viability, and early leaf senescence. RNA sequencing analyses revealed that increased ANAC017 expression leads to higher expression of genes related to mitochondrial stress, cell death/autophagy, and leaf senescence under nonlimiting growth conditions as well as extensive repression of chloroplast function. Gene regulatory network analysis indicated that a complex hierarchy of transcription factors exists downstream of ANAC017. These involve a set of up-regulated ANAC and WRKY transcription factors associated with organellar signaling and senescence. The network also includes a number of ethylene- and gibberellic acid-related transcription factors with established functions in stress responses and growth regulation, which down-regulate their target genes. A number of BASIC LEUCINE-ZIPPER MOTIF transcription factors involved in the endoplasmic reticulum unfolded protein response or balancing of energy homeostasis via the SNF1-RELATED PROTEIN KINASE1 were also down-regulated by ANAC017 overexpression. Our results show that the endoplasmic reticulum membrane tethering of the constitutively expressed ANAC017, and its controlled release, are crucial to fine-tune a fast reactive but potentially harmful signaling cascade. Thus, ANAC017 is a master regulator of cellular responses with mitochondria acting as central sensors.